Current situation and influencing factors of emergency department visits by non-urgent young and middle-aged patients in China: A retrospective study - Wu, Lizhen; Feng, Xiaowei; Dai, Huihua (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Escalating emergency department overcrowding poses a serious threat to healthcare delivery, leading to reduced quality of care, increased risk of infection transmission, and heightened tension between medical staff and patients. Objective: This study aimed to investigate the status of emergency department visits by young and middle-aged patients triaged as non-urgent and to explore the influencing factors. Methods: This study retrospectively analyzed clinical data from 55,578 young and middle-aged patients who visited the emergency department of a tertiary class A hospital in Guangdong Province between January 1 and December 31, 2024. Patients were grouped into urgent and non-urgent based on triage classification. The differences in the clinical indicators between the two groups were compared. Logistic regression analysis was conducted to identify the factors associated with non-urgent triage classification. Results: Among the included young and middle-aged patients, 35,314 (63.5%) were classified as non-urgent cases, while 20,264 (36.5%) were classified as urgent. Binary logistic regression analysis revealed that non-urgent triage classification was significantly associated with the following factors (p < 0.05): visiting Emergency Fever (OR = 1.513) and Emergency Gastroenterology (OR = 4.278) compared to Emergency Internal Medicine and Surgery; arriving on foot or by other modes (OR = 6.073) compared to ambulance transport; visiting during the afternoon shift (OR = 1.110) compared to morning shift, on weekends (OR = 1.111), and during the autumn (OR = 1.140) and winter seasons (OR = 1.083) compared to spring. Conclusion: The rate of non-urgent triage among young and middle-aged patients is high. Triage nurses should be particularly vigilant in assessing patients presenting to departments with a higher likelihood of non-urgent classification, such as the Emergency Fever and Emergency Gastroenterology, as well as those arriving without ambulance transport, during non-working hours and peak flu seasons. These findings can inform nurse-led strategies, such as dynamic staffing and guiding appropriate patients to alternative services, such as internet hospitals, thereby mitigating emergency department overcrowding. It should be noted that in this study, non-urgent status was defined solely by the triage system and was not validated against clinical outcomes; therefore, the findings describe patterns of triage classification rather than objective patient acuity.